Number 11 (October 1981) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1981)
A Revised List of the Freshwater Fishes of Maryland and Delaware. By D.L. Lee et al., 10 pp.
Keywords: freshwater fishes; maryland; delaware